Emergency Department utilization among Deaf American Sign Language users. Issue 4 (October 2015) - McKee, Michael M.; Winters, Paul C.; Sen, Ananda; Zazove, Philip; Fiscella, Kevin
Abstract: Background: Deaf American Sign Language (ASL) users comprise a linguistic minority population with poor health care access due to communication barriers and low health literacy. Potentially, these health care barriers could increase Emergency Department (ED) use. Objective: To compare ED use between deaf and non-deaf patients. Method: A retrospective cohort from medical records. The sample was derived from 400 randomly selected charts (200 deaf ASL users and 200 hearing English speakers) from an outpatient primary care health center with a high volume of deaf patients. Abstracted data included patient demographics, insurance, health behavior, and ED use in the past 36 months. Results: Deaf patients were more likely to be never smokers and be insured through Medicaid. In an adjusted analysis, deaf individuals were significantly more likely to use the ED (odds ratio [OR], 1.97; 95% confidence interval [CI], 1.11–3.51) over the prior 36 months. Conclusion: Deaf American Sign Language users appear to be at greater odds for elevated ED utilization when compared to the general hearing population. Efforts to further understand the drivers for increased ED utilization among deaf ASL users are much needed.